Omphalocele, Exstrophy of Cloaca, Imperforate Anus and Spinal Defect - An Autopsy Report (GAIMS Journal of Medical Sciences, 2023)
Cloacal exstrophy is a rare condition that occurs during the prenatal development of the lower abdominal wall. Cloacal exstrophy isalso known as OEIS Syndrome because of the four features that are typically found together: Omphalocele, Exstrophy of the bladderand rectum, Imperforate anus, Spinal defects.1 We describe a case of 29-year-old female with 3 months’ gestation, her USG showedrudimentary right lower limb and anterior abdominal wall defect for which pregnancy was terminated and fetal autopsy wasperformed. This is a first case report from our institute in which the fetal autopsy finding showed features of OEIS syndrome.